2023
DOI: 10.1021/acs.chemmater.3c01425
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Amide-Linked Covalent Organic Frameworks by N-Heterocyclic Carbene-Mediated Selective Oxidation for Photocatalytic Dehalogenation

Wanqin Wang,
Dekang Huang,
Wenlong Zheng
et al.

Abstract: Linkage conversion of imine to amide can not only boost the stability of covalent organic frameworks (COFs) but also enhance their functionality. However, current methods for generating amide linkages usually involve the use of inorganic oxidants, such as NaClO 2 and oxone, which have a severe drawback of functional group incompatibility. In this study, we introduced a novel synthetic strategy to fabricate amide-linked COFs (Am-COFs) through N-heterocyclic carbene-mediated aerobic oxidation of C�N bonds in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…This offers extensive possibilities for synthesizing COFs with novel structures and functionalities (Figure 4A). [40] For example, imine bonds—the most common COF linkages—can be converted to amide bonds through oxidation with NaClO 2 , [41] KHSO 5 , [42] or N ‐heterocyclic carbene, [43] or to C−N bonds through reduction with NaBH 4 in ice methanol [44] . The Ugi reaction involving imine bonds allows two functional groups to be simultaneously introduced into the framework [45] .…”
Section: Covalent Functionalization Of Cofsmentioning
confidence: 99%
“…This offers extensive possibilities for synthesizing COFs with novel structures and functionalities (Figure 4A). [40] For example, imine bonds—the most common COF linkages—can be converted to amide bonds through oxidation with NaClO 2 , [41] KHSO 5 , [42] or N ‐heterocyclic carbene, [43] or to C−N bonds through reduction with NaBH 4 in ice methanol [44] . The Ugi reaction involving imine bonds allows two functional groups to be simultaneously introduced into the framework [45] .…”
Section: Covalent Functionalization Of Cofsmentioning
confidence: 99%
“…This offers extensive possibilities for synthesizing COFs with novel structures and functionalities (Figure 4A). [40] For example, imine bonds-the most common COF linkages-can be converted to amide bonds through oxidation with NaClO 2 , [41] KHSO 5 , [42] or N-heterocyclic carbene, [43] or to CÀ N bonds through reduction with NaBH 4 in ice methanol. [44] The Ugi reaction involving imine bonds allows two functional groups to be simultaneously introduced into the framework.…”
Section: Linkagesmentioning
confidence: 99%
“…During the preparation of this manuscript, Xiang et al reported a similar approach for the oxidation of imine-based COFs with small organic molecules. [14] Here we would like to report our progress in this area by using NHC as the efficient catalyst. This oxidation has proven to be a versatile and mild synthetic approach for transforming imine-linked COFs to amide-linked COFs.…”
Section: Introductionmentioning
confidence: 99%
“…During the preparation of this manuscript, Xiang et al . reported a similar approach for the oxidation of imine‐based COFs with small organic molecules [14] . Here we would like to report our progress in this area by using NHC as the efficient catalyst.…”
Section: Introductionmentioning
confidence: 99%